2022
DOI: 10.2147/dmso.s348025
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Gastrointestinal Risk Associated with Use of GLP-1 Receptor Agonists: A Real-World Pharmacovigilance Study

Abstract: Background: Glucagon-like peptide-1 (GLP-1) receptor agonists (GLP-1RAs) are promising weight-loss drugs, but real-world data concerning the liability of GLP-1RAs in gastrointestinal safety are lacking. We examined the differences in gastrointestinal safety between semaglutide and liraglutide. Materials and Methods: We used the US Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database and retrieved data during the first three years of semaglutide and liraglutide approved by the FDA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
(44 reference statements)
4
11
1
Order By: Relevance
“…The data on time-to-onset for moderate AEs signals were not significantly different from a recent study, indicating the median durations of nausea, diarrhea and vomiting were 8, 3, and 2 days respectively, in the semaglutide 2.4 mg arm ( 26 ). A real-world pharmacovigilance study of semaglutide had also demonstrated a similar pooled median time-to-onset of gastrointestinal AEs (7 days, IQR 0–48 days), which further supported the findings of our analysis ( 13 ). Hence, careful monitoring in the early period following semaglutide administration might detect most gastrointestinal AEs.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The data on time-to-onset for moderate AEs signals were not significantly different from a recent study, indicating the median durations of nausea, diarrhea and vomiting were 8, 3, and 2 days respectively, in the semaglutide 2.4 mg arm ( 26 ). A real-world pharmacovigilance study of semaglutide had also demonstrated a similar pooled median time-to-onset of gastrointestinal AEs (7 days, IQR 0–48 days), which further supported the findings of our analysis ( 13 ). Hence, careful monitoring in the early period following semaglutide administration might detect most gastrointestinal AEs.…”
Section: Discussionsupporting
confidence: 89%
“…Patient age ( p < 0.001) and body weight ( p = 0.006) rather than sex ( p = 0.251) might be associated with an increased risk of gastrointestinal AEs severity. Semaglutide-associated gastrointestinal AEs seemed to predominately affect females (57.68%) ( Table 1 ), which was in line with the finding that gastrointestinal risks in T2DM occurred more often in females (52.32%) ( 13 ). Further comparison of serious and non-serious cases showed that the proportion of serious AEs was similar in males and females (33.81 vs. 32.31%), and there was no statistical difference between the two groups ( p = 0.251).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations